The acoustics of shock wave lithotripsy - Cleveland, R (2007)
The shock waves employed in lithotripsy are high amplitude acoustics waves. As they propagate through the body to the stone that are affected by coupling to the body and the presence of tissue through which they must pass. Once the shock wave arrives at the stone there is a complex transmission of energy into the stone as the shock wave can couple into compression and shear waves in the stone and produce cavitation in the surrounding fluid. The surrounding tissue is also subject to large physical forces that can result in damage. Physical phenomena that play a role include: generation of sound, nonlinear distortion, attenuation, diffraction, coupling into the body, transmission and mode conversion into the stone. This paper gives a synopsis of some of the relevant physics that applies to shock wave lithotripsy. © 2007 American Institute of Physics.